1998
DOI: 10.1093/bja/80.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal bupivacaine or lidocaine does not provide analgesia after total abdominal hysterectomy

Abstract: We have compared pain scores at rest and on standardized movement, and morphine consumption using patient-controlled analgesia in 60 patients who had undergone total abdominal hysterectomy. Patients were allocated randomly to one of three groups: in the saline group, 0.9% sodium chloride 50 ml was administered into the pelvic cavity before closure of the peritoneum; in the second group, the solution administered was 20 ml of 0.5% bupivacaine solution with epinephrine 1:200,000 diluted with saline to a final vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…In gynaecology, Ali et al 16 found that intraperitoneal delivery of 100 mg 0.5% bupivacaine did not reduce pain in patients undergoing abdominal hysterectomy, whereas Narchi et al 17 reported a decrease in pain after the administration of 100 mg 0.125% bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…In gynaecology, Ali et al 16 found that intraperitoneal delivery of 100 mg 0.5% bupivacaine did not reduce pain in patients undergoing abdominal hysterectomy, whereas Narchi et al 17 reported a decrease in pain after the administration of 100 mg 0.125% bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The ef fects of in tra pe ri to ne al lo cal anesthe tic in fil tra ti on in hyste rec to mi es ha ve be en re por ted, ho we ver the chan ges in the he art ra te and blo od pres su re va lu es ha ve not be en de ter mined. 14,15 Pa in sco res (NS) we re the hig hest in the control gro up, but the different was not sta tis ti cally significant. We ad mi nis te red me pe ri di ne to all pati ents for pos to pe ra ti ve anal ge si a.…”
Section: Discussionmentioning
confidence: 85%
“…The nor ma lity of the da ta dis tri bu ti on was tes ted with Sha pi ro-Wilk test. Be ca u se the dis tri bu ti ons of re pe a ted me a su re ment we re nor mal; by using preo pe ra ti ve (pre-in duc ti on) da ta co-va ri ant, co-va rian ce analy ses (AN CO VA) was used to com pa re se cond (at the 5 th mi nu te af ter the ute ri ne ex ci sion) and third (15 th mi nu te af ter ex tu ba ti on) me asu re ments. Post-hoc Tu key test was used for bi nary com pa ri son.…”
Section: Ma Te Ri Al and Met Hodsmentioning
confidence: 99%
“…74,75 However, a meta-analysis has confirmed the analgesic efficacy of continuous infusion of intraperitoneal local anesthetics. 76 Up to 40% opioid-sparing effects were reported with this technique after open abdominal hysterectomy, 77 with better efficacy using a patient-controlled technique compared with a continuous infusion.…”
Section: Intraperitoneal Local Anestheticsmentioning
confidence: 99%